Organized social complexity : challenge to politics and policy - La Porte, Todd R., 1931- (Princeton University Press, 1975)
One striking feature of modern political and social development has been the construction of social systems encompassing more and more groups. The increase in social complexity, the authors of this volume contend, has reached a point where accepted concepts fail to describe social and political phenomena adequately. The studies in this book reevaluate traditional assumptions. Part One defines organized social complexity and discusses the effects of technological change. Part Two assesses national planning and systems analysis, approaches supposed to provide direct control over social matters. Part Three describes methodological aspects and research applications, and Part Four provides retrospective and prospective views of theories on social complexity.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.